Un fragment de manuscrit inédit du IXe siècle découvert à l’abbaye Saint-Wandrille - Pascal Pradié (Tabularia)
Discovered in the abbey library where it had been used as the cover of an 18th century book, this fragment sheds new light on the production of handwritten material before the Viking invasions.